ANALISIS PENGARUH PROMOSI DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN MELALUI KEPUTUSAN BERTRANSAKSI PADA APLIKASI SHOPEE FOOD DI KOTA MALANG - Muhammad Shoffin Dwiono; Theresia Pradiani; Moh Maskan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research intends to analyze the influence of promotions and service quality on customer satisfaction through transaction decisions on the Shopee Food application in the city of Malang. This type of research is a quantitative research approach. The population in this research is all users of the Shopee Food application in Malang City who have made a purchase transaction at least once during the last one month period. The technique for determining the sample size was Cooper and Emory 100, in this study the sample taken was 100 people. This research uses the Moderated Regression Analysis (MRA) model and Structural Equation Model (SEM) analysis based on Partial Least Square (PLS) with the help of SmartPLS version 3.0. The research results show that: promotional variables have a significant influence on transaction decisions. The service quality variable does not have a significant effect on transaction decisions. Promotion variables do not have a significant effect on customer satisfaction. The service quality variable does not have a significant effect on customer satisfaction. Transaction decision variables have a significant influence on customer satisfaction. Transaction decision variables can mediate the relationship between promotion and customer satisfaction. Transaction decision variables cannot mediate the relationship between service quality and customer satisfaction.